A AMBIGUIDADE LEXICAL DA LIBRAS: UM ESTUDO DESCRITIVO A PARTIR DO INVENTÁRIO NACIONAL DE LIBRAS - Nantes, Janete de Melo (2025)
This dissertation aims at describing and analyzing lexical ambiguity in signs of the Brazilian Sign Language (Libras), based on data from the Inventário Nacional da Libras – Surdos de Referência, integrated with the Libras Signbank. Lexical ambiguity is known as a recurrent phenomenon in natural languages, and it also manifests itself significantly in Libras, although it has been little described from a lexical-semantic perspective that has considere its visual-spatial expertises. The main problem lies in the absence of systematic criteria to distinguish, in sign languages, cases of polysemy and homonymy, mostly when the sign form remains steady while meanings vary according to contextual use. The theoretical framework joins classical studies of lexical semantics (Ullmann, 1971; Barbosa, 2019) with research in sign linguistics (Johnston, Schembri, 2007; Crasborn et al., 2015), to emphasize the notion of phono-semantic parameters such as handshape, movement, and location—as formal units that carry meaning (Johnston e Schembri, 1999). These parameters are conceived here in dialogue with phonesthemes notion (Firth, 1930; Bergen, 2004; Abramova et al., 2013; Smith, 2022), but they are adapted to the visual-spatial modality. This study adopts a qualitative, descriptive, and interpretative approach, focusing on the analysis of signs that share articulatory form but activate different meanings in diverse discursive contexts. The corpus was composed of data from the Portal Libras, transcribed in ELAN and cross-referenced with lexical entries of Libras Signbank. Ambiguities that implicate toponyms, anthroponyms, or variations based solely on mouthing were excluded since they do not take part of the formal scope of lexical analysis. The analysis focused on four representative ambiguous signs: SOLTAR (“release”, “abandon”, “give up”); DIREITO (“legal right”, “school director”, “disability”); ESFORÇAR (“physical effort”, “emotional effort”, “school reinforcement”, “dissertation defense”); and DURO (“rigid sign production”, “hard science”, “difficult exam”). The activated meanings identification, associated to the analysis of phono-semantic parameters and semantic co-occurrents, allowed the classification of uses as polysemy or homonymy, depending on the presence or absence of semantic continuity among meanings. The use of updated glosses, based on the critique of “tyranny of glosses” (Leite et al., 2021), allowed for more precise categorization and respect for the autonomy of Libras as a linguistic system. The results have contributed to the description of Libras lexicon and provide theoretical support for the advancement of linguistic research, as well as practical applications for the training of teachers, translators, and interpreters. They also guide the development of glossaries and pedagogical materials more sensitive to the semantic nuances of the language. Finally, this research highlights the importance of expanding studies on Libras to still underexplored areas, such as the pragmatics of ambiguity, signed onomastics, and the cultural factors that have influenced lexical variation.